Review of conceptual and systematic progress of precision irrigation - Liang, Zhongwei; Liu, Xiaochu; Xiao, Jinrui; Liu, Changhong (International Journal of Agricultural and Biological Engineering, 2021)
Precision irrigation, defined as accurate and appropriate agricultural techniques characterized by optimal management and best collaboration of various irrigation factors, attracts great attention and obtains wide employments in different irrigation conditions or cultivation processes. Moreover, it becomes well-established in major areas of agricultural researches and across the broad spectrum of agricultural techniques especially in specific sectors of scientific frontiers, including soil quality, irrigation scheduling, water resource distribution, crop productivity, tillage management, climate adaptation, and environment monitoring, etc. This paper reviews the research developments and integrated applications of precision irrigation in typical domains of mechanism and performance, covering key aspects such as process optimization, schedule modelling, and effectiveness evaluation, indicating that advanced irrigation optimization methods support higher productivity of crop field and better environmental conditions of soil; Current schedule modelling techniques provide a set of instructive demonstrations and heuristic descriptions for the working principles of precision irrigation and the quantitative assessments of irrigation productivity; The novel investigation on effectiveness evaluation is extremely significant to obtain higher infiltration efficiency, simultaneously to achieve the optimized irrigation qualities for water balance condition, soil water redistribution, and soil moisture uniformity so that the effectiveness quality of irrigation infiltration could be improved remarkably. It is concluded that precision irrigation owns an outstanding collaborating capability and possesses much better working advancement in typical calibration indexes of cultivation accuracy and infiltration efficiency, meanwhile, a high agreement between the predicted and actual irrigation effectiveness could be expected. This novel irrigation review concentrating on the conceptual and systematic progress should be promoted constructively to improve the quality uniformity for precision irrigation and its constructive influences in different applications, and to facilitate the integrated management of agricultural production by higher irrigation efficiency consequently. Keywords: precision irrigation, process optimization, schedule modelling, effectiveness evaluation, conceptual and systematic progress DOI: 10.25165/j.ijabe.20211404.5463 Citation: Liang Z W, Liu X C, Xiao J R, Liu C H. Review of conceptual and systematic progress of precision irrigation. Int J Agric & Biol Eng, 2021; 14(4): 20–31.